Collaborative tax evasion in the provision of services to consumers: A field experiment - Annabelle Doerr; Sarah Necker (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We conduct a field experiment with sellers of home-improvement services on two German online markets. We take the role of consumers and vary whether we request an invoice for the delivery of the service. In a market which allows anyone to sell anonymously, a willingness to evade is prevalent. In a market that keeps track of credentials, sellers are only willing to evade when a willingness to collude is signaled. The evasion discount is in most estimates not larger than the tax subsidy for legal demand. Evasion is unlikely to be beneficial for many consumers in our setting.
Keywords: H26; C93; E26; J22; O17; 330; Collaborative tax evasion; evasion discount; undeclared work; third-party reporting; field experiment